2022
DOI: 10.3389/fpsyg.2022.947916
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Perceived Influence, Virtual Interactivity on Consumer Purchase Intentions Through the Path of Brand Image and Brand Expected Value

Abstract: Many researchers are currently showing interest in researching consumers who are purchasing the products with the help of new tools, and new kinds of markets are emerging rapidly. M-commerce is a prevalent mode of marketing and is famous among young people of Pakistan. Current research is planned to check the status of consumer purchase intentions (PIs) using perceived influence, virtual interactivity, brand image, and brand expected value among customers who purchase their products with the help of m-commerce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 124 publications
0
2
0
Order By: Relevance
“…This validates research conducted by Wu et al, [12] which identified that in the sphere of influencer social media marketing, when follower expectations of a product suggested by an influencer are large, follower intentions to buy the product will also increase. In addition, the results of this study are also in line with research conducted by (Jia et al, [25], which explains that there is a positive influence of brand expected value variables on purchase intention.…”
Section: Hypotesis 6: Pengaruh Brand Expected Value On Purchase Inten...supporting
confidence: 91%
See 1 more Smart Citation
“…This validates research conducted by Wu et al, [12] which identified that in the sphere of influencer social media marketing, when follower expectations of a product suggested by an influencer are large, follower intentions to buy the product will also increase. In addition, the results of this study are also in line with research conducted by (Jia et al, [25], which explains that there is a positive influence of brand expected value variables on purchase intention.…”
Section: Hypotesis 6: Pengaruh Brand Expected Value On Purchase Inten...supporting
confidence: 91%
“…The existence of this research strengthens the research conducted by Castillo & Fernandez [5], which revealed that perceived influence has a positive impact on the expected brand value. As for, this is also in line with Jia et al, [25] which explains that there is a positive perception effect on the value of brand expectations.…”
Section: Hypotesissupporting
confidence: 89%
“…On the other hand, a negative brand image can decrease consumer trust and loyalty, which can lead to lower buying intentions. Additionally, factors such as user-generated content, social media marketing, celebrity endorsement, and product aesthetics can also influence consumer buying intentions through their impact on brand image (Firmanza & Artanti, 2022;Jia et al, 2022;Jiang et al, 2023;Nusairat et al, 2021)…”
Section: Literature Review and Hypothesis Development A Brand Image A...mentioning
confidence: 99%
“…The brand image, according to the consumer's self-image, generates a subjective experience referred to as brand-image congruence or self-image congruence (Royo et al, 2022). A brand's image is the perceptionsconsumers have about a brand as reflected by the brandconnections they have in their minds (Jia et al, 2022;Lie et al, 2022). Marketing programs can generate positive brand image by building a strong relationship between a brand and its image in consumers' memories.…”
Section: Literature Review Brand Imagementioning
confidence: 99%